B-Scan and "En-Face" Spectral-Domain Optical Coherence Tomography Imaging for the Diagnosis and Followup of Acute Retinal Pigment Epitheliitis. (17th February 2013) - De Bats, Flore; Wolff, Benjamin; Mauget-Faÿsse, Martine; Scemama, Claire; Kodjikian, Laurent
Abstract : Purpose . To report B-scan and "En-face" spectral-domain optical coherence tomography (SD-OCT) findings in acute retinal pigment epitheliitis (ARPE). Methods . Two patients (3 eyes) with ARPE were examined. Fluorescein and indocyanine green (ICGA) angiography, B-scan, and "En-face" SD-OCT were performed in each patient at initial and follow-up visits. Results . Both patients presented with acute onset of blurred vision, and one with bilateral involvement. B-can OCT revealed disruption of the macular retinal pigment epithelial (RPE) inner band layer and photoreceptors' inner and outer segment (IS-OS) junction. Hyperreflective dots were observed in the outer nuclear layer (ONL) above the RPE/IS-OS disruption. Just around these hyperreflective dots, slight thickening of the hyperreflective IS/OS junction was observed. During the late phase, indocyanine green angiography (ICGA) showed a macular cockade-like hyperfluorescent halo. "En-face" OCT showed the same cockade-like appearance with a hyporeflective center and a hyperreflective border matching the pattern observed on ICGA. At followup, as vision improved without treatment, B-scan OCT demonstrated progressive resolution of the hyperreflective and disrupted lesions; "en-face" OCT also showed disappearance of the macular cockade-like halo with a transient discrete hyperreflective macular star at the RPE level in one eye. Conclusion . "En-face" OCT associated with B-scan SD-OCT analysis appears to be very helpful in the diagnosis and followup of ARPE. The pathophysiology of ARPE remains complex and still poorly understood. These techniques help define the location and extent of structural damage occurring in this disease.